Immune modulation as a therapeutic strategy in bone regeneration - Schlundt, Claudia (J Exp Orthop, 2015)
We summarize research approaches and findings on bone healing and regeneration that were presented at a workshop at the 60th annual meeting of the Orthopedic Research Society (ORS) in New Orleans in 2014. The workshop was designed to discuss the role of inflammation in bone regeneration in the context of fundamental biology, and to develop therapeutic strategies that involve immune modulation. Delayed or non-healing of bone is a major clinical problem, with around 10% of fracture patients suffering from unsatisfying healing outcomes. Inflammation is traditionally seen as a defense mechanism, but was recently found essential in supporting and modulating regenerative cascades. In bone healing, macrophages and T- and B-cells interact with progenitor cells, bone forming osteoblasts and remodeling osteoclasts. Among the cells of the innate immunity, macrophages are promising candidates for targets in immune-modulatory interventions that would overcome complications in bone healing and bone-related diseases. Among the cells of the adaptive immune system, CD8+ T cells have been shown to have a negative impact on bone fracture healing outcome, whereas regulatory T cells could be promising candidates that have a positive, modulating effect on bone fracture healing. This workshop addressed recent advances and key challenges in this exciting interdisciplinary research field.